1997
DOI: 10.1097/00000539-199703000-00013
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Progressive Anemia on Jejunal Mucosal and Serosal Tissue Oxygenation in Pigs

Abstract: Anemia may promote intestinal hypoxia. We studied the effects of progressive isovolemic hemodilution on jejunal mucosal (Po2muc), and serosal tissue oxygen tension (Po2ser, Clark-type surface electrodes), mucosal microvascular hemoglobin oxygen saturation (Hbo2muc), and hematocrit (Hctmuc; tissue reflectance spectophotometry) in a jejunal segment. Twelve domestic pigs were anesthetized, paralyzed, and mechanically ventilated. Laparatomy was performed, arterial supply of a jejunal segment isolated, and constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
4
15
0
Order By: Relevance
“…This good correlation between PscO 2 and PserO 2 continued throughout all PEEP levels. This is in agreement with other studies indicating very good correlation between these variables in different situations like hypoxic hypoxia [14], haemorrhage [9] and anaemia [25]. These studies also indicate that such a correlation does not exist between PscO 2 and mucosal PO 2 [13,14,25].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This good correlation between PscO 2 and PserO 2 continued throughout all PEEP levels. This is in agreement with other studies indicating very good correlation between these variables in different situations like hypoxic hypoxia [14], haemorrhage [9] and anaemia [25]. These studies also indicate that such a correlation does not exist between PscO 2 and mucosal PO 2 [13,14,25].…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with other studies indicating very good correlation between these variables in different situations like hypoxic hypoxia [14], haemorrhage [9] and anaemia [25]. These studies also indicate that such a correlation does not exist between PscO 2 and mucosal PO 2 [13,14,25]. This is probably due to redistribution of the blood flow within the intestinal wall, in order to maintain mucosal oxygen supply [25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As a result, the pO 2 gap, the difference between the intestinal μpO 2 and P MV O 2 that occurred during shock, persisted after transfusion of the stored RBCs. Several mechanisms have been proposed 29 to explain the discrepancy between microvascular pO 2 and regional venous pO 2 that is observed during hemorrhagic shock 18,19,30 and anemia 31 . The pO 2 gap between mesenteric venous and microvascular blood might be attributed to changes in intramural blood flow redistribution, 31–33 direct diffusion of O 2 from arterioles to venules, 34 or an inability of Hb to offload O 2 to the tissues quickly enough as it passes through the microcirculation 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, lactacidosis occurred in isolated cases, which leads us to assume that the absolutely critical threshold was reached. Animal experiments showed that below 10% Hct systemic and myocardial lactate production commence as a manifestation of oxygen deficiency [24,25]. Deliberate hypotension to a mean arterial pressure of 40-50 mm Hg also contributes to a decrease in intraoperative blood loss.…”
Section: Acute Normovolemic Hemodilution and Deliberate Hypotensionmentioning
confidence: 99%